2021
DOI: 10.1016/j.ijid.2021.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Value of routine whole genome sequencing for Mycobacterium tuberculosis drug resistance detection

Abstract: Routine whole genome sequencing (WGS) of pathogens is becoming more feasible as sequencing costs decrease and access to benchtop sequencing equipment and bioinformatics pipelines increases. This study examined the added value gained from implementing routine WGS of all Mycobacterium tuberculosis isolates in New South Wales, Australia.Drug resistance markers inferred from WGS data were compared to commercial genotypic drug susceptibility testing (DST) assays and conventional phenotypic DST in all isolates seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…While these studies have demonstrated the feasibility of NGS in TB drug resistance diagnosis, the sequencing platforms are either obsoleted (Colman et al, 2016), or the study only focused on AFB positive specimens with limited variability in drug resistance patterns (Smith et al, 2020). More importantly, as most platform focused on whole genome sequencing data, high-quality genomic DNA prepared from MTB isolates are usually required (Lam et al, 2021;Olawoye et al, 2021). The long turnaround time of MTB culture would not be in favor of rapid MTB resistance analysis.…”
Section: Introductionmentioning
confidence: 99%
“…While these studies have demonstrated the feasibility of NGS in TB drug resistance diagnosis, the sequencing platforms are either obsoleted (Colman et al, 2016), or the study only focused on AFB positive specimens with limited variability in drug resistance patterns (Smith et al, 2020). More importantly, as most platform focused on whole genome sequencing data, high-quality genomic DNA prepared from MTB isolates are usually required (Lam et al, 2021;Olawoye et al, 2021). The long turnaround time of MTB culture would not be in favor of rapid MTB resistance analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, mutt gene alleles cause drug resistance and alter bacterial morphology [ [57] , [58] , [59] ]. Numerous pieces of evidence have been reported regarding the relationship between the Beijing genotype and MDR-TB so that this genotype can be considered as a biomarker for drug-resistant TB [ [60] , [61] , [62] ]. We showed for the first time in a comprehensive analysis that the Beijing family is the most predominant genotype among the XDR-TB strains.…”
mentioning
confidence: 99%
“…Our experience has been that phenotypic isoniazid resistance associated with this mutation is only observed when the broth microdilution method (TREK) is used. 41 In contrast, to these findings with inhA and fabG1, most isolates that demonstrated katG mutations did demonstrate phenotypic isoniazid resistance consistent with its association with high level isoniazid resistance. 33 The high specificity of the katG gene mutation for isoniazid resistance along with the high prevalence of Isoniazid resistance in the general population supports its inclusion in rapid molecular tests that are used for screening for resistance.…”
Section: Discussionmentioning
confidence: 78%